Pemanfaatan Pompa Air Tenaga Surya Untuk Sistem Irigasi Pertanian - Muhammad Syahid; Nasaruddin Salam .; Wahyu Piarah .; Jalaluddin .; Rustan Tarakka .; Gaffar Alqadri .; Zuryati Djafar . (Faculty of Engineering UNHAS, 2022)
Solar energy is a renewable and environmentally friendly energy that can be utilized in various fields. Solar energy can be used to increase production in the agricultural sector by introducing smart and efficient technological interventions with cheap energy sources. One of the problems faced by farmers is the provision of crop irrigation and watering which requires a lot of labor or high electricity costs. With a solar-based irrigation pump with an automation system, it is expected to reduce the need for labor and electricity costs. The method of service is by conducting training on the implementation of solar water pumps for agricultural irrigation systems for HKTI-Gowa Youth. The training was continued by demonstration of the use and working system of a solar water pump machine for an agricultural irrigation system using an automation system based on a timer. This service provides additional knowledge about the use of solar power for agricultural irrigation systems, so that it can be more efficient and effective with this cheap and environmentally friendly energy source. This activity was highly appreciated by the training participants in this service.